Groin injuries in soccer: incidence, prevalence and risk factors - Alabbad, M. A.; Nuhmani, S.; Muaidi, Q. I. (Journal of Physical Education Research, 2019)
Groin injury is very common in soccer due to the characteristics of the sport in which athletes require quick acceleration, deceleration and the sudden changing of their body direction during playing the sport. Adductor muscles are considered the most frequently injured structure in the groin region as it plays an important role as a stabiliser for the hip joint. This literature review is aimed to manifest the magnitude of the incidence and prevalence of the groin injuries, the risk factors and differential diagnoses that affect the decision making towards groin related injuries. However, studies in this area have revealed that 12-16% of all injuries per season are related to groin injuries and during the season they show that there are 4.7 injuries per 1,000 playing hours, 12.1 for match injuries and 2.7 for training injuries. Only 5% of the groin injuries are sustained due to improper play. Nevertheless, Understanding the groin area anatomy is extremely important because it helps to discriminate between the two musculoskeletal pathologies and non-musculoskeletal pathologies.